Literature Review: The Influence of Social Stigma on Children with Intellectual Disabilities - Salwa Hanan Midiyati; Medina Izzaty; Nahla Hayaatun Nufus; Tania Nur Anisa Ramadhani; Makhsun Intikhon; Citra Ashri Maulidina; Mohammad Arif Taboer (Universitas Negeri Surabaya, 2025)
Social stigma against children with intellectual disabilities has serious impacts, including exclusion, discrimination, and psychological distress. This study applies a Systematic Literature Review approach to analyze 10 selected articles focusing on forms of stigma, its effects, and mitigation strategies. The findings show that stigma affects not only the children but also their families. Effective strategies to reduce stigma include public education, teacher training, social support, and inclusive policy implementation. Cross-sector collaboration is essential to create a more inclusive and stigma-free environment.